From malaise to well-being: a diagnosis of the mental attitude of school teachers - García Jarrín, Mario Hildebrando (2024)
This academic essay seeks to bring the reader closer to the problem of unrest among teachers and we analyze the possible causes and consequences of such a situation, emphasizing the role of every school, regardless of its sponsorship, as a public service and how unrest that affects teachers, a fundamental part of the teaching process, is transferred from school to society in general. The definition of well-being and discomfort in schools is identified and I continue with the Freudian definition of discomfort, of why discomfort affects the entire society; public and private schools and why the school should be considered a public good, the discontent of teachers and the discontent of students, causes of teacher discontent and consequences of discontent among teachers. The development of the text begins with the identification of the problem (social, but, in the case of the present study, also psychological), followed by the determination of the thesis and the arguments of the study, the development of each of them and finally the conclusions and recommendations.